Studi Speed Drop dan Pengaruhnya terhadap Stabilitas Beban Sistem Governor - Muhammad Yusuf Nurfani (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Hydroelectric Power Plants (HPP) are a type of power plant that utilizes renewable energy from water flow. The hydroelectric system works by converting the kinetic energy of flowing water into mechanical energy, which is then converted into electrical energy. Water flows through a penstock directed towards the turbine, where it strikes the turbine blades, causing rotation. To maintain the stability of the turbine's rotational speed at the Maninjau HPP, a governor system is used. The Maninjau HPP consists of four generating subunits with a nominal rotational speed of 600 rpm. The governor system functions to stabilize the turbine's rotation at the nominal speed of 600 rpm, as the speed affects the generator's output frequency. The stabilization process is carried out by adjusting the Guide Vane openings, which are the blades surrounding the turbine. The Maninjau HPP has a speed drop of 3%, with a frequency reduction of 1.5 Hz. Additionally, a frequency change of 0.1 Hz will result in a load change of 0.13 MW.